Oxidative Stress is Increased in Serum from Mexican Patients with Relapsing-Remitting Multiple Sclerosis - Ortiz, Genaro Gabriel (IOS Press, 2009)
Objective: To determine the oxidative stress markers in serum from patients with relapsing-remitting multiple sclerosis. Methods: Blood samples from healthy controls and 22 patients 15 women (7 aged from 20 to 30 and 8 were > 40 years old) and 7 men (5 aged from 20 to 30 and 2 were > 40 years old) fulfilling the McDonald Criteria and classified as having Relapsing-Remitting Multiple Sclerosis accordingly with Lublin were collected for oxidative stress markers quantification. Results: Nitric oxide metabolites (nitrates/nitrites), lipid peroxidation products (malondialdehyde plus 4-hidroxialkenals), and glutathione peroxidase activity were significantly increased in serum of subjects with relapsing-remitting multiple sclerosis in comparison with that of healthy controls. These data support the hypothesis that multiple sclerosis is a component closely linked to oxidative stress.